THE ТYPOLOGICAL SPECIFICITIES OF PARTY SYSTEMS - Сутула, О. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The article is devoted to historical observation of the main theoretical and methodological foundations of the party systems approach. The evolution of the criteria for party systems' classification is analyzed. It was found that the most commonly used criterion for the classification of party systems is the number of competing parties, measured by indicator of the effective number of parties. It's argued that modern Ukrainian party system is to classify not by an ideological principles, but by its functional features, which characterizes it as an quasi-party system.